2014
DOI: 10.3390/met4010008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism-Structure Correlations during the ε→τ Transformation in Rapidly-Solidified MnAl Nanostructured Alloys

Abstract: Magnetic and structural aspects of the annealing-induced transformation of rapidly-solidified Mn 55 Al 45 ribbons from the as-quenched metastable antiferromagnetic (AF) ε-phase to the target ferromagnetic (FM) L1 0 τ-phase are investigated. The as-solidified material exhibits a majority hexagonal ε-MnAl phase revealing a large exchange bias shift below a magnetic blocking temperature T B~9 5 K (H ex~1 3 kOe at 10 K), ascribed to the presence of compositional fluctuations in this antiferromagnetic phase. Heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The structure and magnetic properties of the MnAl system have been widely studied because the microstructural changes and defects introduced during the metastable -phase transformation highly influence its magnetic properties. Studies have reported various techniques to prepare MnAl-based alloys, including hot extrusion, melt spinning, mechanical alloying, mechanical milling (MM), cryomilling, and gas-atomization [8,9,[17][18][19][20][21][22][23]. Ball milling is a well-known technique used for microstructure refinement and strain inducement, but also for promotion of metastable phase formation.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and magnetic properties of the MnAl system have been widely studied because the microstructural changes and defects introduced during the metastable -phase transformation highly influence its magnetic properties. Studies have reported various techniques to prepare MnAl-based alloys, including hot extrusion, melt spinning, mechanical alloying, mechanical milling (MM), cryomilling, and gas-atomization [8,9,[17][18][19][20][21][22][23]. Ball milling is a well-known technique used for microstructure refinement and strain inducement, but also for promotion of metastable phase formation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, coercivity development has been managed in MnAl particles through proper optimization of the phases coexisting in the material and induced microstructural strain [ 18,19 ]. The low cost and wide availabilities of Mn and Al in combination with a good machinability, high modulus of elasticity and excellent corrosion resistance complete the characteristics required for making of this material an excellent rare earth-free PM candidate [ 15,20 ]. In addition to all these benefits, MnAl shows a reduced density of 5200 kg/m 3 by comparison with 7600 kg/m 3 for Nd 2 Fe 14 B, which will lead to lighter PMs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research show that the τ-phase is formed through a two-step process, originating from the parent hexagonal ɛ-phase that transforms into the intermediate B19-structure ɛ’-phase which in turn transforms into the τ-phase if sufficient undercooling is achieved at 723 K < T < 823 K 16 , 17 . These transformations are believed to occur independently of the composition and are controlled by nucleation and growth processes 17 .…”
Section: Introductionmentioning
confidence: 99%
“…These transformations are believed to occur independently of the composition and are controlled by nucleation and growth processes 17 . It has been shown that the transformation is highly dependent on the nucleation of the τ-phase at the interphase with the ɛ-phase 16 .…”
Section: Introductionmentioning
confidence: 99%